2015
DOI: 10.22458/urj.v7i1.864
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of the Indian Major Carp, Labeo rohita (Cypriniformes: Cyprinidae) from six drainages of Ganga basin, India

Abstract: ABSTRACT:The Indian Major Carp, Labeo rohita, is a geographically widespread and economically important food fish species in tropical freshwater of India and adjacent countries. We studied the lengthweight relationships of 1 033 specimens collected from the main channel of Ganga river and its five major drainages from March 2009 to July 2012. The length of males ranged from 16 to 92cm (females: 16 to 94cm). The growth is allometric positive (b>3) for males, females and pooled sexes. The coefficient of determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Also it is well known that the functional regression b value represents the body form and is directly related to the weight affected by ecological factors habitat, area, seasonal effects, degree stomach fullness, gonad maturity, sex, health, preservation techniques and differences in the observed length ranges of the captured specimens 29,17,18 (Ricker, 1973. Several workers reported positive allometric growth in freshwater fish; notable among them are 20,34,23,9,19,45,30,42,35 in Cirrhina mrigala, Catla catla, Labeo bata, Labeo rohita, Pristolepis fasciata, Pangasius pangsius, Pseudorasbora parva and Macrognathus aculeatus respectively. The greater value of 'b' mainly depends on shape and fatness of individuals of fish.…”
Section: Discussionmentioning
confidence: 99%
“…Also it is well known that the functional regression b value represents the body form and is directly related to the weight affected by ecological factors habitat, area, seasonal effects, degree stomach fullness, gonad maturity, sex, health, preservation techniques and differences in the observed length ranges of the captured specimens 29,17,18 (Ricker, 1973. Several workers reported positive allometric growth in freshwater fish; notable among them are 20,34,23,9,19,45,30,42,35 in Cirrhina mrigala, Catla catla, Labeo bata, Labeo rohita, Pristolepis fasciata, Pangasius pangsius, Pseudorasbora parva and Macrognathus aculeatus respectively. The greater value of 'b' mainly depends on shape and fatness of individuals of fish.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that S. d. denticulatus formed the annual ring once in Xijiang River and matured in 4-5 years under culture conditions (Jiang & Yu, 2003;Wang et al, 2010). The growth rate of S. d. denticulatus is relatively lower than that of other carp species, including Labeo rohita, Cyprinus carpio, Ctenopharyngodon Idella, Spinibarbus sinensis and Spinibarbus yunnanensis (Iqbal Mir et al, 2013;Pokhrel, 2020;Yang & Chen, 1994;Zeng et al, 2017). Therefore, selecting individuals with high growth rate would be essential for breeding and conservation of S. d. denticulatus.…”
mentioning
confidence: 99%